MicroRNA‐10a controls airway smooth muscle cell proliferation via direct targeting of the PI3 kinase pathway. Issue 5 (12th February 2014) - Hu, Ruoxi; Pan, Wenchi; Fedulov, Alexey V.; Jester, William; Jones, Matthew R.; Weiss, Scott T.; Panettieri, Reynold A.; Tantisira, Kelan; Lu, Quan
ABSTRACT: Airway smooth muscle (ASM) cells play important physiological roles in the lung, and abnormal proliferation of ASM directly contributes to the airway remodeling during development of lung diseases such as asthma. MicroRNAs are small yet versatile gene tuners that regulate a variety of cellular processes, including cell growth and proliferation; however, little is known about the precise role of microRNAs in the proliferation of the ASM. Here we report that a specific microRNA (miR‐10a) controls ASM proliferation through directly inhibiting the phosphoinositide 3‐kinase (PI3K) pathway. Next‐generation sequencing identified miR‐10a as the most abundant microRNA expressed in primary human airway smooth muscle (HASM) cells, accounting for > 20% of all small RNA reads. Overexpression of miR‐10a reduced mitogen‐induced HASM proliferation by 50%, whereas inhibition of miR‐10a increased HASM proliferation by 40%. Microarray profiling of HASM cells expressing miR‐10a mimics identified 52 significantly down‐regulated genes as potential targets of miR‐10a, including the catalytic subunit α of PI3K ( PIK3CA ), the central component of the PI3K pathway. MiR‐10a directly suppresses PIK3CA expression by targeting the 3'‐untranslated region (3'‐UTR) of the gene. Inhibition of PIK3CA by miR‐10a reduced V‐akt murine thymoma viral oncogene homolog 1 (AKT) phosphorylation and blunted the expression of cyclins and cyclin‐dependent kinases that are required for HASM proliferation. Together, our study identifies a novel microRNA‐mediated regulatory mechanism for PI3K signaling and ASM proliferation and further suggests miR‐10a as a potential therapeutic target for lung diseases whose etiology resides in abnormal ASM proliferation.—Hu, R., Pan, W., Fedulov, A. V., Jester, W., Jones, M. R., Weiss, S. T., Panettieri, R. A., Jr., Tantisira, K., Lu, Q. MicroRNA‐10a controls airway smooth muscle cell proliferation via direct targeting of the PI3 kinase pathway. FASEB J . 28, 2347–2357 (2014). www.fasebj.org